Problem fields in mathematics teaching. Part 3, Views of Finnish seventh-grades about mathematics teaching - Pehkonen, Erkki (Research report / Department of Teacher Education, University of Helsinki, 1992)
Tiivistelmä: Probleemakentät matematiikan opetuksessa. Osa 3 : Suomalaisten seitsemäsluokkalaisten näkemyksiä matematiikan opetuksesta.
Keywords: ongelmanratkaisu; matematiikka; opetus; oppiminen; didaktiikka